Characterization of vaccine-induced immune responses against coccidiosis in broiler chickens. Issue 28 (21st June 2022) - Gaghan, Carissa; Adams, Daniel; Mohammed, Javid; Crespo, Rocio; Livingston, Kimberly; Kulkarni, Raveendra R.
Abstract: Coccidiosis, caused by Eimeria protozoan species, is an economically important enteric disease of poultry. Although commercial live vaccines are widely used for disease control, the vaccine-induced protective immune mechanisms are poorly characterized. The present study used a commercial broiler vaccine containing a mixture of E. acervulina, E. maxima, and E. tenella . One-day-old chicks were vaccinated by spray followed by a challenge at 21 days of age with a mixture of wild type Eimeria species via oral gavage. Oocyst shedding, immune gene expression and cellular responses in the spleen and cecal tonsils were measured at pre- (days 14 and 21) and post-challenge (days 24, 28 and 35) time points. Results showed that the oocyst counts were significantly reduced in the vaccinated chickens at post-challenge compared to unvaccinated control group. While the vaccinated birds had a significantly increased toll-like receptor (TLR) 21 gene expression at pre-challenge, the transcription of interferon (IFN)γ, Interleukin (IL)-12 and CD40 genes in spleen and cecal tonsils of these birds was significantly higher at post-challenge compared to unvaccinated chickens. Cellular immunophenotyping analysis found that vaccination led to increased frequency of macrophages and activated T cells (CD8 + CD44 + and CD4 + CD44 + ) in the spleen and cecal tonsils at post-challenge. Furthermore, in vitro stimulation of chicken macrophages (MQ-NCSU cells) with purified individual species of E. acervulina, E. maxima, and E. tenella showed a significantly increased expression of TLR21, TLR2 and IFNγ genes as well as nitric oxide production. Collectively, these findings suggest that TLR21 and TLR2 may be involved in the immune cell recognition of Eimeria parasites and that the vaccine can induce a robust macrophage activation leading to a T helper-1 dominated protective response at both local and systemic lymphoid tissues.